2016
DOI: 10.4081/cp.2016.865
|View full text |Cite
|
Sign up to set email alerts
|

A Child with Debilitating Pruritus

Abstract: We describe a case of two-year-old boy presenting with debilitating pruritus, patchy alopecia and jaundice since the age of 6 months. On evaluation he had intrahepatic cholestasis with persistently raised serum alkaline phosphatase, normal Gamma glutamyl transferase and raised serum bile acid levels. His liver biopsy showed bland cholestasis and electron microscopy showed granular bile suggestive of progressive familial intrahepatic cholestasis type I. Medical therapy with ursodeoxycholic acid, cholestyramine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This protein is a constituent of various healthy tissues, including the heart, muscle, liver, kidney, and brain. However, under favorable conditions, it can also become pathogenic in these tissues (Sonthalia et al, 2016;Martıńez-Naharro et al, 2018;Pinto et al, 2021;Deng et al, 2022;Gurung and Li, 2022). Furthermore, previous studies have confirmed that human amyloid and bacterial amyloid share many common features, undoubtedly warranting a more in-depth analysis (Das et al, 2022;Bessho et al, 2023).…”
Section: Microbial Factors In the Pathogenesis Of Crohn's Diseasementioning
confidence: 96%
“…This protein is a constituent of various healthy tissues, including the heart, muscle, liver, kidney, and brain. However, under favorable conditions, it can also become pathogenic in these tissues (Sonthalia et al, 2016;Martıńez-Naharro et al, 2018;Pinto et al, 2021;Deng et al, 2022;Gurung and Li, 2022). Furthermore, previous studies have confirmed that human amyloid and bacterial amyloid share many common features, undoubtedly warranting a more in-depth analysis (Das et al, 2022;Bessho et al, 2023).…”
Section: Microbial Factors In the Pathogenesis Of Crohn's Diseasementioning
confidence: 96%
“…However it has not been showed to be useful in children with PFIC1-2. The recommended dose of cholestyramine is 240 mg/kg/day PO, in three divided doses [26].…”
Section: Treatmentmentioning
confidence: 99%